Tecido ósseo e implantes dentais caracterização mecânica e biológica em condições de normalidade e submetidos à radiação ionizante - Soares, Priscilla Barbosa Ferreira (2015)
The bone is a connective resilient tissue in continuous modification process. This tissue may be adversely affected by action of ionizing radiation, compromising the healing process and osseointegration. The integration between bone and implant is modulated by the surface of dental implants. This study aimed to evaluate overall by mechanical and histomorphometric characterization of bone tissue and its integration to the dental implants in normal conditions and when subjected to ionizing radiation. This study was divided into five specific objectives; specific objective 1: generate, through dynamic indentation test protocol to measure the Vickers hardness and the modulus of elasticity of the periimplantar bone using blocks performed by bone/implant extracted by the rabbit s tibias; specific objective 2: to evaluate the stability and osseointegration of dental implants with different surface treatments by measuring the resonant frequency and histomorphometric analysis quantifying the contact bone/implant and area fraction occupied by bone implants installed in the tibia of rabbits after periods of 2 and 4 weeks; specific objective 3: to assess the effect of ionizing radiation on tibias of rabbits modulated by the time elapsed from the application of ionizing radiation on the force to fracture, work to failure and stiffness of bone tissue measured by 3-bending flexural strength test, on the Vickers hardness and elastic modulus calculated by means of dynamic indentation test, and on the cortical bone thickness, bone volume and bone porosity percentage measured by microCT and quantification of osteocytes lacunarity, measured by histological evaluation; specific objective 4: to evaluate the effects of ionizing radiation on previous installed and osseointegrated implants by association of different methods involving Vickers hardness and modulus of elasticity measured by dynamic indentation; implant/bone stability measured by pull-out test, the thickness of cortical bone, volume of bone tissue, and percentage of bone porosity measured by microCT; specific objective 5: generate manuscript that summarize the main findings of specific objective 1, 2, 3 and 4 designated to Brazilian clinical fulfilling the social function of knowledge generation. After analyzing the results it can be concluded that the dynamic indentation method proved to be highly useful for individualized characterization of the periimplantar bone tissue. The implant surfaces with different wettability are capable of producing adequate integration bone / implant installed using instrumentation normal condition. Radiation therapy negatively affected the mechanical and structural properties of bone tissue. In areas rehabilitated with dental implant, the radiotherapy reduced partially the stability of implant/bone interface, thereby reducing the mechanical properties of the periimplantar bone tissue, mainly that bone tissue located close to implant surface, which can compromise the long-term prognosis.